Expectations of Elementary School/Madrasah Ibtidaiyah teachers in Mataram City on the Implementation of the 2022 Prototype Curriculum - Arif Widodo; Linda Feni Haryati; Asri Fauzi; Lalu Wira Zain Amrullah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The relatively fast curriculum changes in the last two decades have caused a lot of noise in its implementation. One element that is quite affected by this change is the teacher. Not a few teachers find it difficult to implement the new curriculum when there is a change in the curriculum. One of the discourses launched by the government in the field of education in 2022 is the application of a prototype curriculum at all levels of education, including the elementary school level. This study aims to determine how teachers' expectations of government discourse in implementing the prototype curriculum in elementary schools. The object of study in this study was elementary and Islamic elementary school teachers. The research location is in Mataram City, West Nusa Tenggara. The type of research used is descriptive qualitative. Data collection using interviews. Through this research, it is expected to find a picture of how teachers expect the discourse of implementing the prototype curriculum in elementary schools. The results showed that teachers had very high expectations of the prototype curriculum. Teacher expectations for the curriculum include the curriculum being able to improve the shortcomings of the previous curriculum, making it easier for teachers in the learning process, and being able to improve the quality of learning after the pandemic.